Breaking the Culture-specific Silence of Women Glass Bead Makers in Ghana: Towards Empowerment - Dickson Adom; Samuel T. Daitey; Lily Yarney; Peggy A. Fening (Elsevier, 2020)
Background: The production of glass beads in Ghana is greatly impacted by the ingenuity of Ghanaian women. Preliminary investigations revealed the lack of interest on the part of women due to poor working conditions as a result of the influence of culture-specific silence. Therefore, the study investigated the poor working conditions faced by these industrious women with the ultimate goal of suggesting ways they can be empowered. Methods: A phenomenological study was conducted in two indigenous glass bead communities in Ghana. Data were solicited via direct observations, personal interviews and focus group discussions. Twenty-six purposively sampled respondents were recruited for the study. Data from the study were analyzed using Interpretative Phenomenological Analysis. Results: The results confirmed that the elderly women glass bead makers are much influenced by the Ghanaian culture of silence. This prevents the women from speaking about the challenges they are facing in their work. Also, the women are silenced because of the fear of losing their jobs as well as the reluctance of their male managers to remedy the challenges they encounter in the course of work. This has resulted in poor remuneration, lack of insurance packages for workers, certification, and absence of personal protective tools for the women. Conclusion: The study tasks the government of Ghana, the Legal Advocacy for Women in Africa (LAWA), the Fair Wages and Salaries Commission in Ghana, the Ghana Trade Union as well as the Local Government Workers' Union to empower the women to sustain the glass bead industry in Ghana.